2020
DOI: 10.7759/cureus.8354
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Malignant Melanoma Mimicking Mammary Mass: A Rare Presentation

Abstract: Breast lump in perimenopausal women is considered a primary malignancy unless proved otherwise. Metastasis to the breast from extramammary sites is rare. Malignant melanoma (MM) is known for its ability to spread to distant sites, which can be both hematogenous and lymphatic. The common sites are skin, lung, liver, brain, etc. However, reports of melanoma metastasizing to the breast are rare. We present a case of 50-year-old female patient, who underwent wide local excision and split skin grafting for MM right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Although the presence of microcalcification in the mammographic evaluation of various metastatic malignancies (hepatocellular carcinoma, carcinomas of gastric or ovarian origin) is reported in the literature, it is not a very common finding. 12 , 13 In our study, radiological preliminary diagnoses were malignant in 80% and benign neoplasia in 13.3% of the cases.…”
Section: Discussionsupporting
confidence: 47%
“…Although the presence of microcalcification in the mammographic evaluation of various metastatic malignancies (hepatocellular carcinoma, carcinomas of gastric or ovarian origin) is reported in the literature, it is not a very common finding. 12 , 13 In our study, radiological preliminary diagnoses were malignant in 80% and benign neoplasia in 13.3% of the cases.…”
Section: Discussionsupporting
confidence: 47%
“…While non-mammary metastases to the breast is therefore considered to be rare, a case series report by DeLair et al has reported that MM was the most common extra-mammary metastatic tumour and represented 22% of all cases of non-mammary metastases to the breast [ 12 ]. The majority of those melanoma cases arose in cutaneous sites and three of the cases were ocular in origin [ 12 , 13 ]. In our particular case, however, the patient did not have any obvious cutaneous or ocular lesions that could be connected to her malignancy.…”
Section: Discussionmentioning
confidence: 99%